Overlapping and enzyme-specific contributions of matrix metalloproteinases-9 and -12 in IL-13–induced inflammation and remodeling - Lanone, Sophie (American Society for Clinical Investigation, 2002)
IL-13 potently stimulates eosinophilic and lymphocytic inflammation and alveolar remodeling in the lung, effects that depend on the induction of various matrix metalloproteinases (MMPs). Here, we compared the remodeling and inflammatory effects of an IL-13 transgene in lungs of wild-type, MMP-9–deficient, or MMP-12–deficient mice. IL-13–induced alveolar enlargement, lung enlargement, compliance alterations, and respiratory failure and death were markedly decreased in the absence of MMP-9 or MMP-12. Moreover, IL-13 potently induced MMPs-2, -12, -13, and -14 in the absence of MMP-9, while induction of MMPs-2, -9, -13, and -14 by IL-13 was diminished in the absence of MMP-12. A deficiency in MMP-9 did not alter eosinophil, macrophage, or lymphocyte recovery, but increased the recovery of total leukocytes and neutrophils in bronchoalveolar lavage (BAL) fluids from IL-13 transgenic mice. In contrast, a deficiency in MMP-12 decreased the recovery of leukocytes, eosinophils, and macrophages, but not lymphocytes or neutrophils. These studies demonstrate that IL-13 acts via MMPs-9 and -12 to induce alveolar remodeling, respiratory failure, and death and that IL-13 induction of MMPs-2, -9, -13, and -14 is mediated at least partially by an MMP-12–dependent pathway. The also demonstrate that MMPs-9 and -12 play different roles in the generation of IL-13–induced inflammation, with MMP-9 inhibiting neutrophil accumulation and MMP-12 contributing to the accumulation of eosinophils and macrophages.